Additive manufacturing of ZrO2 ceramic dental bridges by stereolithography. Issue 1 (2nd January 2018) - Lian, Qin; Sui, Wenquan; Wu, Xiangquan; Yang, Fei; Yang, Shaopeng
Abstract : Purpose: This paper aims to develop an additive manufacturing technique for complex zirconia ceramic dental bridges. Design/methodology/approach: To carry out this study, a dental bridge model was obtained by three-dimensional reverse engineering, and a light-curable zirconia ceramic suspension was formulated. Zirconia bridges were manufactured by stereolithography and then treated by vacuum freeze drying, vacuum infiltration and sintering. The optimal scanning speed was determined according to the shape precision comparison. Then, characteristics of the sintered ceramic parts were tested as size shrinkage, relative density, surface Vickers hardness, surface roughness and microstructure. Findings: The method for preparation of light-curable zirconia suspension (40 volume per cent solid loading) with a viscosity value of 127 mPa·s was proposed. The optimal laser scanning speed for zirconia bridge fabrication was 1200 mm/s. A relative density of 98.58 per cent was achieved; the obtained surface Vickers hardness and surface roughness were 1, 398 HV and 2.06 µm, respectively. Originality/value: This paper provides a potential technical method for manufacturing complex zirconia dental bridges and other small complex-shaped ceramic components which are difficult to be made by other manufacturing techniques.